2017
DOI: 10.1093/ntr/ntx035
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Snus Alters Heart Rate Variability in the Infant

Abstract: The results indicate that smokeless tobacco (Swedish snus) affects the developing autonomic nervous system during gestation. Even if exposure is interrupted during the first or second trimester, effects in autonomic cardiac regulation are seen in the 1-2 month-old infant. This underlines the importance of abstaining from all types of tobacco use during the whole pregnancy. Our findings may also have more general relevance to other routes by which nicotine can be delivered to a fetus and newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 40 publications
2
34
1
Order By: Relevance
“…Swedish snus contains merely nicotine, and its use during pregnancy has been associated with increased risks of stillbirth, preterm birth, neonatal apnoea, impaired heart rate variations and oral cleft malformations . Interestingly, an earlier study showed that the frequency of breastfeeding was lower not only among smoking, but also snus using mothers than among nontobacco using mothers . This further supports the findings of Bertini et al.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Swedish snus contains merely nicotine, and its use during pregnancy has been associated with increased risks of stillbirth, preterm birth, neonatal apnoea, impaired heart rate variations and oral cleft malformations . Interestingly, an earlier study showed that the frequency of breastfeeding was lower not only among smoking, but also snus using mothers than among nontobacco using mothers . This further supports the findings of Bertini et al.…”
supporting
confidence: 82%
“…Safety studies on electronic cigarettes in pregnancy are still lacking, and data on nicotine replacement therapy are difficult to interpret due to poor compliance. Swedish snus contains merely nicotine, and its use during pregnancy has been associated with increased risks of stillbirth, preterm birth, neonatal apnoea, impaired heart rate variations and oral cleft malformations (6)(7)(8)(9)(10). Interestingly, an earlier study showed that the frequency of breastfeeding was lower not only among smoking, but also snus using mothers than among nontobacco using mothers (10).…”
mentioning
confidence: 99%
“…The calculation was based on the highest amount for each category and the category of more than seven pouches was estimated as 56 mg. Smoking was quantified similarly (<1, 1-5, 6-10, [11][12][13][14][15][16][17][18][19][20] or >20 cigarettes per day) with an estimated nicotine dose of 2 mg per cigarette (16).…”
Section: Questionnairementioning
confidence: 99%
“…All infant controls had cotinine levels <0.7 ng/mL, snus group ranged from 0 to 408 ng/mL and the cigarette smoking group from 0 to 129 ng/mL. In this study, it was apparent that tobacco, regardless of form, timing and type of exposure, could affect the developing infant .…”
Section: Resultsmentioning
confidence: 63%
“…Adverse effects of snus use in pregnancy were observed in several human studies, as outlined in Table 2, with effects of smoking and snus during pregnancy reported in 10 cohort studies (7,(10)(11)(12)(13)(14)(15)(16)(17) and in one study based upon sibling analysis (18). Furthermore, one case report describing neonatal withdrawal symptoms after exposure to around 20 doses of snus per day during pregnancy was identified (19).…”
Section: Adverse Effects Of Snusmentioning
confidence: 99%